Migration and Statistics - Sonja Haug (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2009)
The field of empirical migration and integration research is characterised by a wide range of research questions, theoretical approaches and data sets. Research based on official statistics has to deal with different data sets on migration and foreign population resulting in different numbers. Developments in official statistics concentrate on the improvement of data quality. The census 2010/2011 or the projected central population register are important issues, e.g. in respect of sampling and weighting of migrants in surveys. The concept of migration background in the microcensus is a mayor enhancement in population statistics and has become widely accepted. It is recommended to implement questions on migration background in the census 2010/2011 too. The most important accessible data sets in the field of empirical integration research are the microcensus and the German Socio-Economic Panel; there is still untapped potential for analysis in this area. The supplementation of large surveys with a migrant sample is an appreciated trend. Most important challenges for empirical migration and integration research are the development of sampling methods for migrant population (including onomastics and topomastics), studies on new and small migrant groups, research projects in the country of origin, longitudinal migrant surveys and the development of measurement instruments.
Keywords: 330; Population; Migration; Integration; Migration Background